Kebijakan Tata Ruang Berbasis Inklusifitas Aktor - Supriadi Takwim; Sitti Rabiatul Wahdaniyah Herman (Departemen Ilmu Pemerintahan Fisip Unhas, 2021)
Abstract This article wants to see how the actor-based inclusive spatial planning policy takes place in the village. The reason is, since decades of development in the village, especially since the law no. 6 of 2014 is getting more massive. Villages are forced to reconstruct existing spatial policies, by adjusting to more modern development patterns. There is a village development orientation which on the one hand abandons traditional values ​​and at the same time moves towards a more modern development. However, the problem is that spatial policies, especially those related to development, often clash with traditional values ​​that exist in the village. Development in the village often involves actors in the village who are involved in protracted conflicts. The inclusion and exclusion of actors is something that will be encountered in many development schemes in the village. By using an approach approach, the researchers used data collection methods in the form of interviews and field observations to find out how the dynamics of development occurred in spatial planning policies. The analytical tool used in this research is to use an actor inclusiveness approach by looking at the policy of the spatial arena as the analysis space in this article